Estudo cinético da degradação térmica e catalítica de petróleo pesado usando Al-MCM-41 - Oliveira, Aline Araújo Alves de (2013)
The mesoporous nanostructured materials have been studied for application in the oil industry, in particular Al-MCM-41, due to the surface area around 800 to 1.000 m2 g-1 and, pore diameters ranging from 2 to 10 nm, suitable for catalysis to large molecules such as heavy oil. The MCM-41 has been synthesized by hydrothermal method, on which aluminum was added, in the ratio Si/Al equal to 50, to increase the generation of active acid sites in the nanotubes. The catalyst was characterized by X-ray diffraction (XRD), surface area by the BET method and, the average pore volume BJH method using the N2 adsorption, absorption spectroscopy in the infrared Fourier Transform (FT-IR) and determination of surface acidity with application of a probe molecule - n-butylamine. The catalyst showed well-defined structural properties and consistent with the literature. The overall objective was to test the Al-MCM-41 as catalyst and thermogravimetric perform tests, using two samples of heavy oil with API º equal to 14.0 and 18.5. Assays were performed using a temperature range of 30-900 ° C and heating ratios (β) ranging from 5, 10 and 20 °C min-1.The aim was to verify the thermogravimetric profiles of these oils when subjected to the action of the catalyst Al- MCM-41. Therefore, the percentage ranged catalyst applied 1, 3, 5, 10 and 20 wt%, and from the TG data were applied two different kinetic models: Ozawa-Flynn-Wall (OFW) and Kissinger-Akahrira-Sunose (KAS).The apparent activation energies found for both models had similar values and were lower for the second event of mass loss known as cracking zone, indicating a more effective performance of Al-MCM-41 in that area. Furthermore, there was a more pronounced reduction in the value of activation energy for between 10 and 20% by weight of the oil-catalyst mixture. It was concluded that the Al-MCM-41 catalyst has applicability in heavy oils to reduce the apparent activation energy of a catalyst-oil system, and the best result with 20% by weight of Al-MCM-41